Pengaruh Kepemimpinan Instruksional Kepala Sekolah, Lingkungan Kerja, dan Supervisi Manajerial terhadap Kinerja Guru Sekolah Dasar - Rebon, Ririn Riana; Wijayanti, Wiwik (Lembaga Teewan Journal Solutions, 2026)
Teacher performance is a key factor in improving the quality of education, influenced by principal leadership, work environment, and supervision. This study aimed to identify the influence of principals' instructional leadership, work environment, and managerial supervision on elementary school teachers' performance in North Bontang District, both partially and simultaneously. A quantitative explanatory research design with a survey method and causal-correlational nature was employed. The population consisted of 239 public elementary school teachers, and total sampling was applied so that the entire population served as respondents. Data were collected using questionnaires that had been tested for validity and reliability, then analyzed using multiple linear regression in SPSS after prerequisite tests were satisfied. The results showed that: (1) instructional leadership significantly influenced teacher performance (t = 22.285; Sig. = 0.000); (2) work environment significantly influenced teacher performance (t = 13.863; Sig. = 0.000); (3) managerial supervision significantly influenced teacher performance (t = 13.946; Sig. = 0.000); and (4) all three variables simultaneously influenced teacher performance (F = 965.942; Sig. = 0.000; R² = 0.925). All hypotheses were accepted, confirming that the three variables play important roles in improving elementary school teachers' performance in the post-pandemic period.